Cholangiocytes derived from human induced pluripotent stem cells for disease modeling and drug validation - Sampaziotis, Fotios; Cardoso de Brito, Miguel; Madrigal, Pedro; Bertero, Alessandro; Saeb-Parsy, Kourosh; Soares, Filipa A.C.; Schrumpf, Elisabeth; Melum, Espen; Karlsen, Tom H.; Bradley, J. Andrew; Gelson, William T.H.; Davies, Susan; et al. (Nature Publishing Group, 2015)
The study of biliary disease has been constrained by a lack of primary human cholangiocytes. Here we present an efficient, serum-free protocol for directed differentiation of human induced pluripotent stem cells into cholangiocyte-like cells (CLCs). CLCs show functional characteristics of cholangiocytes, including bile acids transfer, alkaline phosphatase activity, γ-glutamyl-transpeptidase activity and physiological responses to secretin, somatostatin and vascular endothelial growth factor. We use CLCs to model in vitro key features of Alagille syndrome, polycystic liver disease and cystic fibrosis (CF)-associated cholangiopathy. Furthermore, we use CLCs generated from healthy individuals and patients with polycystic liver disease to reproduce the effects of the drugs verapamil and octreotide, and we show that the experimental CF drug VX809 rescues the disease phenotype of CF cholangiopathy in vitro. Our differentiation protocol will facilitate the study of biological mechanisms controlling biliary development, as well as disease modeling and drug screening.